Coordenação robusta da proteção de redes de média tensão em parques eólicos - Mariana Mendes Guimarães (2024)
Relay protection coordination is the process of selecting and arranging protective relays to restrict the effects of abnormal conditions in power electrical systems. The most economically viable way to detect them and minimize their damage is by installing protection devices. The protection function is efficient when detecting even small changes in the current (sensitivity), disconnecting the smallest possible area from the network (selectivity), and operating systematically when necessary. In addition, the whole process must take place in the shortest possible time (agility). Therefore, each relay should act quickly and keep coordinating well with other devices on the network. This study aims to find robust solutions for the overcurrent relay coordination problem in Dynamic Medium-Voltage Networks. A new nonlinear mathematical model is presented. Its novelty consists of considering the characteristic curves of relays as a variable and including new constraints and penalties in the objective functions related to the operating maximum time allowed. Furthermore, a new objective function is presented, including two terms that minimize the actuation time of the backup relays and violations in the maximum actuation time allowed for each primary relay. The proposed hybrid tool integrates the Differential Evolution algorithm with Linear Programming and an intelligent rounding operator to achieve two objectives: minimizing relay actuation time and maximizing the robustness of protection in scenarios with topological changes arising from line disconnections caused by one, two, or three simultaneous faults. The experiments were carried out to coordinate the relays installed at the Aracati Wind Complex, owned by Companhia Alupar, in the state of Ceará. From the real system, in operation, eleven scenarios were subjected to optimization, which differed by characteristics related to the characteristic curves, the objective function, and the fault conditions. The results indicate a good performance of the tool and the implementations carried out in the mathematical model. Solutions that consider inverse time parameters as variables achieved 60% better performance than those in which the normally inverse curve is a parameter for coordination. The inclusion of backup relay actuation times proved to be very important as the number of primary/backup pairs is much higher than the number of relays. The reductions reached 97% when compared to the model that does not include these times in the objective function. In robust coordination, the energy not supplied was reduced by up to 70%, which indicates the robustness of the solution found. This reduction would be capable of supplying 104 households. New studies are under development to ensure the scalability of the coordination tool and to expand the scope of the problem also to offshore wind plants